Phenotypic and functional analysis of bovine peripheral blood dendritic cells before parturition by a novel purification method - Zhuang, Tao; Urakawa, Megumi; Sato, Hidetoshi; Sato, Yuko; Taguchi, Teruaki; Umino, Tsuyoshi; Katto, Shiro; Tanaka, Koutaro; Yoshimura, Kozue; Takada, Naokazu; Kobayashi, Hiroko; Ito, Megumi; et al. (Animal science journal, 2018)
Dendritic cells (DCs) are specialized antigen presenting cells specializing in antigen uptake and processing, and play an important role in the innate and adaptive immune response. A subset of bovine peripheral blood DCs was identified as CD172a+/CD11c+/MHC (major histocompatibility complex) class II+ cells. Although DCs are identified at 0.1%–0.7% of peripheral blood mononuclear cells (PBMC), the phenotype and function of DCs remain poorly understood with regard to maintaining tolerance during the pregnancy. All cattle used in this study were 1 month before parturition. We have established a novel method for the purification of DCs from PBMC using magnetic‐activated cell sorting, and purified the CD172a+/CD11c+ DCs, with high expression of MHC class II and CD40, at 84.8% purity. There were individual differences in the expressions of CD205 and co‐stimulatory molecules CD80 and CD86 on DCs. There were positive correlations between expression of cytokine and co‐stimulatory molecules in DCs, and the DCs maintained their immune tolerance, evidenced by their low expressions of the co‐stimulatory molecules and cytokine production. These results suggest that before parturition a half of DCs may be immature and tend to maintain tolerance based on the low cytokine production, and the other DCs with high co‐stimulatory molecules may already have the ability of modulating the T‐cell linage.